Diseño de una máquina fumigadora para riego en cultivos de cebolla junca (2021)
Fumigation is the most effective method that farmers have for the control and elimination of pests and infections in crops. This technique is carried out with specialized equipment that transmits a chemical mixture in the form of small drops that are sprayed both on the stem and on the leaves of the plants. The present degree work proposes a machine composed of seven systems that help to solve one of the biggest problems that operators face when carrying out their daily tasks. The main reason behind the development of this device is the prevention of different types of illnesses and injuries caused by overloads to which workers are exposed. In this order of ideas, it was sought to design a sprayer that required the least amount of physical effort in the cultivation of Junca onion.